Dorsal venous foot ulcer caused by an intermetatarsal perforating vein - Obermayer, A.; Göstl, K. (Phlebologie, 2008)
This case report describes a woman (age: 79 years) with a recurrent venous ulcer located on the left dorsal foot. Duplex investigation showed that this ulcer was caused by an intermetatarsal insufficient perforating vein (PV). Finally Duplex-guided sclerotherapy of the causing PV has been chosen as therapy and the ulcer was successfully healed.
Keywords: Perforator; foot ulcer; venous insufficiency; foam sclerotherapy; surgery